2009
DOI: 10.1159/000251184
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Adrenal Tumors: A Single-Center Experience with 238 Cases

Abstract: Objective: It was the aim of this study to review and analyze clinical data on the diagnosis and management of patients with adrenal masses. Patients and Methods: Between 1976 and 2005, 238 patients admitted to our institute with adrenal masses were reviewed. Incidence, clinical features, imaging technique findings, surgical approaches, morbidity and mortality, as well as pathological diagnoses were reported. Results: The series comprised 134 males and 104 females (mean age 33.3 ± 20.3 years). Right-sided mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Porpiglia et al [9] reported a high frequency of neighborhood repeat or port-site seeding after laparoscopic adrenalectomy for threatening injuries. In a case series of Gomha et al [13], investigating the treatment of adrenal tumors with 238 cases, 5 masses of adrenal harm were overseen laparoscopically. Three masses were confined metastases from bladder, liver, and bosom growths while 2 were essential adrenal tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Porpiglia et al [9] reported a high frequency of neighborhood repeat or port-site seeding after laparoscopic adrenalectomy for threatening injuries. In a case series of Gomha et al [13], investigating the treatment of adrenal tumors with 238 cases, 5 masses of adrenal harm were overseen laparoscopically. Three masses were confined metastases from bladder, liver, and bosom growths while 2 were essential adrenal tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Also, laparoscopic adrenalectomy has been ended up to be superior in both pediatric and morbid obese cases [16]. Gomha et al [13] uncovered an essentially shorter healing center stay with matched complication rate in the laparoscopic approach regardless of being used in smaller-sized adrenal masses. In our study, supporting and similar to the literature, the average operative time was around 80 minutes that ranged between 55 and 190 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery remains the primary treatment modality and the only chance for cure in these patients [11,12,13]. However, the role of laparoscopic adrenalectomy (LA) in the treatment of patients with AC is controversial.…”
Section: Discussionmentioning
confidence: 99%